The Effect of Educational Intelligent Technologies on the Academic Achievement of Elementary Students in Shiraz District One - Hashemi, Seyyed Ahmad; Nabavizadeh, Zahra (IJRDO- Journal of Educational Research, 2017)
The present study was conducted to determine the effect of using Educational Intelligent Technologies on the academic achievement of primary school students in Shiraz District one. The method of this study was semi-experimental, pre-test and post-test with control group. The population of this study was elementary school students in Shiraz District one, which 80 students were selected through a census method from schools equipped with Educational Intelligent Technologies facilities. After the pre-test, the content of the course was presented in eight sessions using intelligent technology and also traditionally for the experimental group, and finally, the academic achievement questionnaire with the same questions from the two groups was done. Based on the statistical sample, 80 questionnaires have been distributed. All of the questionnaires are valid and can be cited for data analysis. The research tool in this study included two researcher-made questionnaires of Educational Intelligent Technologies and Valerand Students’ Educational Achievement. The validity of the questionnaires was evaluated based on the experts’ opinion and also on the basis of Bartlett’s test. The Educational Intelligent Technologies Questionnaire had a reliability of 0.765 and academic achievement of 0.742 and their reliability based on Cronbach’s alpha coefficient for Intelligent Learning Inventory was 0.712. And academic achievement was estimated to be 0.894, which indicates the desirable reliability of the research questionnaire. In this study, linear regression analysis and Friedman test have been used. The results of this study showed that Educational Intelligent Technologies has a significant effect on the educational achievement of elementary school students in Shiraz District one.